What is philosophy? - Deleuze, Gilles 1925-1995; Guattari, Félix 1930-1992 (London Verso, 2011)
This work examines what it means to be a philosopher and attacks the sterility of modern philosophy. Part One explores the nature and scope of philosophy and its relation to social and economic development. Part Two considers other forms of thought: science, art, literature and music.